Macrophage polarization in diabetic wound healing. Issue 1 (29th December 2022) - Wu, Xingqian; He, Wenjie; Mu, Xingrui; Liu, Ye; Deng, Junyu; Liu, Yiqiu; Nie, Xuqiang
Abstract: Impaired wound healing is one of the severe complications of diabetes. Macrophages have been shown to play a vital role in wound healing. In different wound environments, macrophages are classified into two phenotypes: classically activated macrophages and alternatively activated macrophages. Dysregulation of macrophage phenotypes leads to severely impaired wound healing in diabetes. Particularly, uncontrolled inflammation and abnormal macrophage phenotype are important reasons hindering the closure of diabetic wounds. This article reviews the functions of macrophages at various stages of wound healing, the relationship between macrophage phenotypic dysregulation and diabetic wound healing and the mechanism of macrophage polarization in diabetic wound healing. New therapeutic drugs targeting phagocyte polarization to promote the healing of diabetic wounds might provide a new strategy for treating chronic diabetic wound healing.